Creation of Own Reserves for Own Shares in the Acquisition of Own Shares for Withdrawal by Simplified Procedure under Slovenian Law where the Consideration is Paid in Instalments - Drnovšek, Gregor (LeXonomica, 2018)
During the process of withdrawing own shares, the rules that are relevant, among others, to their acquisition by the company are regulations governing the creation of reserves for own shares. The regulations are clear in cases where the company acquires their own shares simultaneously with the payment of the purchase price. This article will pertain to the proper application of these regulations according to Slovenian law, specifically in cases where the company pays the purchase price for their own shares, which it intends to withdraw after acquisition, in instalments, and acquires their own shares only after paying the last instalment of the purchase price.